The role of sustainability in nuclear energy plans—What do national energy strategies tell us?. (December 2016) - Gralla, Fabienne; John, Beatrice; Abson, David J.; Møller, Anders P.; Bickel, Manuel; Lang, Daniel J.; von Wehrden, Henrik
Highlights: Energy strategies were assessed based on 56 facets of sustainability across 7 dimensions. There is a lack of comprehensive definitions of sustainability in energy strategy documents. Energy strategies would benefit from greater stakeholder involvement. Risk and social aspects of sustainability were mentioned less than other facets of sustainability. Abstract: Energy supply and use play vital roles in transition towards a sustainable society. Nuclear energy is used or planned to be used in 40 countries globally, yet the contribution of nuclear energy to sustainable development remains an area of contention. The purpose of this exploratory study is to understand the framing of sustainability within national energy strategies of countries pursuing or planning to start nuclear energy production. The strategies were analyzed by assessing the occurrence of 56 facets of sustainability grouped into 7 dimensions. In addition, the definitions of sustainability used in the strategies and the information on consultation and public participation in their preparation was reviewed. Most strategies mentioned sustainability but did not provide its explicit definition. Risk, waste management and social aspects of sustainability were mentioned relatively less frequently than to environmental, governance and economic aspects of sustainability. The information on consultation and public participation portrayed a limited extent of such processes.